(3TQM GdCfehPLs - (3GdCQOHjdj GdQhej, LeGd GdOjf, Zfj RGOg, eMeO Hf YHO GdZfj, J (B647 (3g`s ((3CHh GdbGSe Hf NOGhQOjs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3deG QCjJ eNJUQ GdEeGe (B... (3GYfj GfehPLg aj GdfMh bdjd GddaX cKjQ GdeYfi UZjQ GdGdMLe YRjR GdaMhi eQZhHG ddeHJOFjf (B...s
(3BNQgG (B:s
... (3def GHJdj HHdjI UMHI GdCVOGO YUefG Gddg ef TQhQge hQO Edjge HdaX hef cjO aLhQge hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\211s
(3cTa GdXfhf (B1\ 185s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs